Comparision of Efficacy of Esmolol and Lignocaine for Attenuation of Hemodynamic Stress Response to Laryngoscopy and Tracheal Intubation in Patients Undergoing Laparoscopic Cholecystectomy Under General Anaesthesia (Journal of Nobel Medical College, 2024)
Background: Laryngoscopy and tracheal intubation results in intense sympathoadrenal response characterized by hypertension, tachycardia and arrhythmia. There are many pharmacological and non-pharmacological method are being employed to attenuate the response. The aim of our study is to compare the efficacy of intravenous bolus dose of esmolol with lignocaine in attenuating the hemodyanamic response to laryngoscopy and tracheal intubation.Materials and Methods: The study is prospective comparative study. One hundred six patients of both sex, aged 18-65 years, belonging to the American Society of Anesthesiologists physical Status I and II randomly allocated into two groups (n = 53). The study drugs diluted in 10‑ml normal saline. Group I received esmolol 1.5 mg/kg and Group II received lignocaine 1.5 mg/kg 2 min before laryngoscopy and intubation. The heart rate, systolic blood pressure, diastolic blood pressure and mean arterial blood pressure were noted at basal, during intubation, and 1, 2, 3, and 5 min after intubation. Data were represented by mean standard deviation and graphs. Students T-test was used to compare mean between groups.Results: The mean pulse rate, mean of mean arterial pressure at intubation and at 1, 2, 3, and 5 min after intubation in lignocaine group showed a significant rise in these values but in esmolol group it remained nearer to or less than baseline values.Conclusion: Esmolol 1.5 mg/kg is effective in attenuating the pressor response in comparison with lignocaine 1.5 mg/kg during laryngoscopy and intubation.